The Anuario ThinkEPI celebrates its 18th anniversary - Arroyo-Vázquez, Natalia; Goyanes, Manuel; Olea, Isabel (Anuario ThinkEPI, 2024)
The Anuario ThinkEPI celebrates its eighteenth anniversary with this new issue, and does so maintaining the same spirit with which it was born, in 2007, by the hand of Tomàs Baiget: the analysis of trends in information and documentation, to which communication has been added later, through brief notes and open peer review. In order to analyze it is necessary to confront different realities, ideas and points of view, so the Anuario has always encouraged debate among professionals and academics.